Hydrogenated monolayer graphene with reversible and tunable wide band gap and its field-effect transistor - Jangyup Son (Nature Portfolio, 2016)
The absence of a band gap in graphene hinders its use in electronics. Here, the authors open a band gap as large as 3.9 electronvolts in graphene grown by chemical vapour deposition by treating it in hydrogen plasma, and then use this material to create a room temperature field- effect transistor.